The Psychology of Driving on Rural Roads Development and Testing of a Model - Weller, Gert.; SpringerLink (Online service) (Wiesbaden : VS Verlag für Sozialwissenschaften, 2010)
Rural roads constitute the most dangerous road category with regard to the number of fatal accidents. In order to increase traffic safety on rural roads it is necessary to take into account not only their inherent properties but also their effect on behaviour. Gert Weller develops a psychological model for driving on rural roads which is validated in three empirical steps: laboratory, simulator and driving experiments. His results provide insight into the possibilities of how driving behaviour on rural roads can be influenced and give practical guidance for the enhancement of rural road safety. The book is written for psychologists in the fields of traffic psychology and human factors research, traffic engineers, road planners as well as for political decision makers in traffic planning departments.
Driving on Rural Roads: The Current Situation -- Applying Existing Models to Driving on Rural Roads -- A Psychological Model for Driving on Rural Roads -- Empirical Validation -- Empirical Validation: Summary and Conclusions.
Keywords: Philosophy (General).; Psychology; Psychology, general; Psychology, general